2015
DOI: 10.1091/mbc.e14-11-1502
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule agonists of mammalian Diaphanous–related (mDia) formins reveal an effective glioblastoma anti-invasion strategy

Abstract: Formin agonists impede the most dangerous aspect of glioblastoma—tumor spread into surrounding healthy tissue. Formin activation impairs a novel aspect of the transformed cell and informs the development of antitumor strategies for a cancer needing a more effective therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 82 publications
5
41
0
Order By: Relevance
“…Two major effector proteins of RhoA, RhoB, and RhoC GTPases are the mammalian homolog of Drosophila diaphanous (mDia, belonging to the formin protein family) and Rho‐associated coiled‐coil forming kinase (ROCK), which are associated with migration in gliomas (Arden et al, ; Xue et al, ). ROCK has been implicated in the abovementioned nuclear squeezing and glioblastoma cell invasion in ex vivo brain slices (Beadle et al, ).…”
Section: Malignant Alterations Of Glioma Cells Increase Their Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two major effector proteins of RhoA, RhoB, and RhoC GTPases are the mammalian homolog of Drosophila diaphanous (mDia, belonging to the formin protein family) and Rho‐associated coiled‐coil forming kinase (ROCK), which are associated with migration in gliomas (Arden et al, ; Xue et al, ). ROCK has been implicated in the abovementioned nuclear squeezing and glioblastoma cell invasion in ex vivo brain slices (Beadle et al, ).…”
Section: Malignant Alterations Of Glioma Cells Increase Their Invasionmentioning
confidence: 99%
“…In addition, direct cell-cell contacts and especially ECM-receptors drive glioma cell migration and invasion. Key components of this phenomenon are invadopodia, glioma-ECM interactions, and the production of proteases and glycosidases that facilitate invasion by ECM-degradation kinase (ROCK), which are associated with migration in gliomas (Arden et al, 2015;Xue et al, 2016). ROCK has been implicated in the abovementioned nuclear squeezing and glioblastoma cell invasion in ex vivo brain slices (Beadle et al, 2008).…”
Section: Cytoskeleton Cell Signaling Drives Invasivenessmentioning
confidence: 99%
“…FMNL3 is a newly discovered gene whose encoded product belongs to the DRFs family . Some studies showed that FMNL3 is highly expressed in a variety of malignant tumors and is associated with poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…Its encoded product, FMNL3, is classified among the diaphanous‐related formins (DRFs). DRFs are currently some of the most potent actin nucleation factors and are involved in many actin‐based life processes, including cell adhesion, cell movement, cytokinesis, morphological changes, and formation of cell polarity . As one of the important members of the DRFs subgroup, there are also reports that FMNL3 participates in cell‐cell adhesion and promotes cell migration, promoting the invasion and metastasis of various malignant tumors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation